Comprehensive Detection and Isolation of Fault in Complicated Electrical Engineering - Zhang, Yagang; Zhao, Zheng; Wang, Zengping (Elektronika ir Elektrotechnika, 2013)
In this paper, real time dynamic information of complicated electrical engineering provided by phasor measurement units to analyze and locate the fault is utilized. Based on fuzzy cluster analysis theory and the principle of minimum expected cost of misclassification, we have explored a comprehensive detection and isolation system of fault in complicated electrical engineering. It has been proved by a large number of simulation experiments that the comprehensive fault detection and isolation system can accurately and reliably detect and isolate faults and provide guarantee for the safety and stable operation of electrical power and energy system. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5646